Entre o sagrado e o profano: os efeitos de sentido nos testemunhos do blog evangélico do Bispo Edir Macedo - Torres, João Victor Costa (2014)
The testimonial is a way of statement that demonstrates or admit the existence of a reality with which the enunciator has contacted. This is, thus, pushed to say what he saw, heard or touched. In this paper, we verified the effects of senses produced in the blog of Bishop Macedo, founder of the Universal Church of the Kingdom of God (UCKG), from a corpus which consists of nine testimonies of presumed believersselected among 64 statements distributed during the year, 2012. Instead of instantaneous testimonials, on a live presentation, these media narratives are underpinned by attributes such as hyperlinks, visuals, language translators, besides mechanisms of interaction and sharing in other spheres from mediatic slant. The problem of this analysis was born from the observation of regular points in the discursive architecture of these testimonials, when was identified the existing relation force between the sacred and the profane, everyday practices. During six months, analysis of the empirical material, we found some effects of the senses on the testimonials, as the dialectic structure and the need for denuding a precarious past, an engagement to shield the figure of Macedo and the UCKG towards society; a update of a crusade against other religions; and the presence of certain sensuality in self-deprecation of the deponents, and an unequal relation of forces (sacred and profane) in the construction of truth. In order of succeeding in this investigation, we used the theoretical and methodological assumptions of Analysis of French Discourse (AD), denouncing the qualitative nature of the research. As a methodological principle, we still use transdisciplinarity, which validated some of our dialogues, especially with philosophy. The conception of discourse modeled by a media support and transpassed by the subject(s) and story (ies) characterized the perspective of the research